Alterations in exon 1 of c-myc and expression of p62c-myc in cervical squamous cell carcinoma. Issue 11 (November 1997) - O'Leary, J J; Landers, R J; Crowley, M; Healy, I; Kealy, W F; Hogan, J; Doyle, C T
Abstract : AIMS: To examine human papillomavirus (HPV) positive and negative squamous cell carcinomas of the cervix for structural alterations in exon 1 c-myc; and to investigate the expression pattern of p62, the protein product of c-myc. MATERIAL: Archival paraffin wax embedded tissues of cervical squamous cell carcinomas, stage I and II, retrieved from the files of the department of pathology, University College Cork, Ireland: 40 cases were examined for alterations in exon 1 of c-myc; 57 cases were used for immunocytochemical p62 analysis. METHODS: c-myc exon 1 PCR on HPV positive and negative stage I and II cervical squamous cell carcinomas was performed using primers designed to fragile sites in exon 1 of the c-myc oncogene, which are frequently involved in translocation phenomena and deletions in other neoplasms. This region is bordered by two promoter sequences P1 and P2. In addition, the expression of p62 was evaluated using the monoclonal antibody Mycl-9E10. RESULTS: Alterations in exon 1 of c-myc were shown in 7.5% of squamous cell carcinomas of the cervix. Changes in exon 1 and 2 of c-myc were also found in COLO 320 cells and Raji cells. These alterations were due to small deletions within exon 1 of c-myc, but point polymorphisms occurring within the priming sites (in one case) may also have occurred. The alterations uncovered appeared "clonal, " as replicate samples showed the same amplicon band pattern. Expression of c-myc was variable, with cytoplasmic staining patterns predominating. All cases which showed exon 1 alterations were HPV positive and had strong nuclear positivity on p62 immunocytochemistry. CONCLUSIONS: Alterations in exon 1 of c-myc occur in a minority of cervical cancers and there was increased expression of p62 in a cohort of HPV positive and negative cervical squamous cell carcinomas. Exon 1 alterations may provide an alternative route to c-myc activation in early squamous cell carcinoma.